IL-6 signaling drives self-renewal and alternative activation of adipose tissue macrophages - Ackermann, Jan; Arndt, Lilli; Fröba, Janine; Lindhorst, Andreas; Glaß, Markus; Kirstein, Michaela; Hobusch, Constance; Wunderlich, F. Thomas; Braune, Julia; Gericke, Martin (Frontiers in Immunology, 2024)
Introduction Obesity is associated with chronic low-grade inflammation of adipose tissue (AT) and an increase of AT macrophages (ATMs) that is linked to the onset of type 2 diabetes. We have recently shown that neutralization of interleukin (IL)-6 in obese AT organ cultures inhibits proliferation of ATMs, which occurs preferentially in alternatively activated macrophage phenotype. Methods In this study, we investigated AT biology and the metabolic phenotype of mice with myeloid cell-specific IL-6Rα deficiency (Il6raΔmyel) after normal chow and 20 weeks of high-fat diet focusing on AT inflammation, ATM polarization and proliferation. Using organotypical AT culture and bone marrow derived macrophages (BMDMs) of IL-4Rα knockout mice (Il4ra-/-) we studied IL-6 signaling. Results Obese Il6raΔmyel mice exhibited no differences in insulin sensitivity or histological markers of AT inflammation. Notably, we found a reduction of ATMs expressing the mannose receptor 1 (CD206), as well as a decrease of the proliferation marker Ki67 in ATMs of Il6raΔmyel mice. Importantly, organotypical AT culture and BMDM data of Il4ra-/- mice revealed that IL-6 mediates a shift towards the M2 phenotype independent from the IL-6/IL-4Rα axis. Discussion Our results demonstrate IL-4Rα-independent anti-inflammatory effects of IL-6 on macrophages and the ability of IL-6 to maintain proliferation rates in obese AT.